Blood profile of implantation stainless steel 316L local implant material on rat femoral bone - . Gustian; H. Soehartono; N. Jujur; A.H. S. Wargadipura; D. Noviana (Indonesian Center for Animal Research and Development (ICARD), 2018)
This study was aimed to obtain information regarding complete blood count (CBC) profile of post implantation of stainless steel (SS) 316L as an Indonesian local product of non-degradable metal implant. Thirty adult male rat, aged approximately 12 weeks were divided into 3 groups, i.e. control group without implantation, implant group with import SS316L and implant group with Indonesian national local SS316L that developed by Agency for the Assessment and Application of Technology (BPPT). The implant groups were given implants by inserting it between femoral bone and biceps femoris muscle. On the control group, defect was made on bone without inserting an implants material. Examination of the systemic response was done with CBC before and 30 days after implantation. The analysis of red blood cells amount, haemoglobin level, haematocrite value, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), total white blood cell and its differentiation from each group did not show significant differences. In conclusion, stainless steel 316L of import and national local product showed non-negative effects on blood profile.